Forecasting price index of finger millet (Eleusine coracana) in India under policy interventions - LAMA, ACHAL; SINGH, K N; SHEKHAWAT, RAVINDRA SINGH; SARKAR, KRISHNA PADA; GURUNG, BISHAL (The Indian Journal of Agricultural Sciences, 2020)
Millets are the major substitute for cereals such as rice and wheat. For developing country like India, millets hold immense importance as the cost of production is low and has high nutritional values. Various policy interventions are made by government of India from time to time to popularise its consumption and production. Few major policy interventions were made in last decade and inclusion of coarse cereals under Food Security Bill is one among them. Keeping this in mind, the present study was carried out at ICAR- Indian Agricultural Statistics Research Institute, New Delhi during 2018 to know the impact of policy interventions on the price index of Ragi. Further, we have introduced these interventions in the model using structural break analysis. The volatile Ragi price index series were modelled and forecasted using popular class of Generalised Autoregressive Conditional Heteroscedastic (GARCH) models and its asymmetric extensions. The results indicated improvement in modelling and forecasting performance of the models after incorporation of the policy interventions. Study has empirically highlighted the positive impact of policies introduced.